2022
DOI: 10.3390/su141610411
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Effects of Biochar on Microbial Ecological Function in Soil and Crop Quality

Abstract: Biochar, a late-model environmental functional material, has been widely applied in environmental remediation, agricultural production, and energy utilization due to its excellent characteristics such as porosity and high specific surface area. In recent years, many studies on the effects of biochar on agricultural soil and crop quality have been performed. The application of biochar can influence soil microbial status directly or indirectly by changing the physicochemical properties of soil. Apart from increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Asfaw et al [7] found a high root colonisation level of arbuscular mycorrhizal fungi as a result of biochar application. In addition, the biochar indirectly affected the growth and metabolic activity of soil microbes by altering the soil properties, regulating nutrient availability, and regulat-ing enzyme activity [30]. Overall, our results demonstrate the potential role of biochar application in improving soil microbe growth and reproduction in soil.…”
Section: Discussionmentioning
confidence: 60%
“…Asfaw et al [7] found a high root colonisation level of arbuscular mycorrhizal fungi as a result of biochar application. In addition, the biochar indirectly affected the growth and metabolic activity of soil microbes by altering the soil properties, regulating nutrient availability, and regulat-ing enzyme activity [30]. Overall, our results demonstrate the potential role of biochar application in improving soil microbe growth and reproduction in soil.…”
Section: Discussionmentioning
confidence: 60%
“…More importantly, the combination of biochar (600 kg/ha) and nitrogen fertilizer (105 kg/ha and 126 kg/ha) significantly increased the contents of soil microbial biomass carbon and nitrogen compared with the control (biochar 0 kg/ha and N fertilizer 105 kg/ha and 126 kg/ha). This can be attributed to the synergistic effect of biochar and fertilizer and may also be because biochar can adsorb nitrogen and other nutrients, creating a nutrient-rich microenvironment and providing ideal conditions for microbial growth ( Ullah et al., 2020 ; Zhao et al., 2022 ). However, in this study, the content of soil microbial biomass carbon and nitrogen under the combined application of high biochar (1200 kg/ha) and low nitrogen fertilizer (105 kg/ha) was significantly lower than that in the combined application of high biochar (1200 kg/ha) and high nitrogen fertilizer (126 kg/ha), which may be related to the soil C/N ratio and needs further in-depth study.…”
Section: Discussionmentioning
confidence: 99%
“…Azeem et al [87] revealed that biochar can promote plant development resulting from improved microbial activity in the soil through its impact on microbial abundance, bacteria/fungi ratio, and microbial community structure. Zhang et al [88,89] and Zhao et al [90] similarly observed enhanced soil microbial biomass of up to 763% with biochar application.…”
Section: Effect Of Biochar On Soil Microbial Populationmentioning
confidence: 96%